Integration and decentralization: the evolution of Dutch regional land policy. Issue 2 (2nd April 2016) - van Straalen, Fenje M.; van den Brink, Adri; van Tatenhove, Jan
ABSTRACT: The implementation of planning objectives in the public interest depends on the land laws and land policies of a state. Public stakeholders are not only enabled or constrained in their actions by these laws and policies, they also (re)formulate these laws and policies to support their actions. The objective of this paper is to understand how different stakeholders in spatial development processes influence land policy dynamics (both the (re)formulation and the implementation of policies) and vice versa. The paper explores the changes in land policies in the Netherlands, in particular how changes have enabled the regional planning level. The Policy Arrangement Approach is used to analyse the strategic behaviour of agencies and their use of structure in spatial development processes. The findings show that the arrangement rapidly changed from the 1980s onwards, due to changes in the underlying political discourses and the effectuation of these discourses via regulation and instruments. With objectives of decentralization and integration, the national government has enabled the regional planning level to become more active in spatial development processes. Although the provinces were enabled by new laws and policies, this did not significantly change their role within the Dutch planning system.